The Scoraig wind trials – In situ power performance measurements of locally manufactured small wind turbines. Issue 3 (June 2021) - Leary, Jon; Piggott, Hugh; Howell, Robert
This article presents new insight into the real-world performance of a range of open source locally manufactured small wind turbines designed to enable sustainable rural electrification. The power performance of seven machines was measured in situ and compared to wind tunnel, test site and other in situ data to produce a set of generic power curves. This article shows that the shape and size of the curve (and therefore the energy that will be generated) varies considerably. However, over-performance was just as likely as under-performance, validating the designer's predicted energy yields. Nonetheless, optimising the power curve by tuning the small wind turbine increased energy yields by up to 156%. Developing low-cost practical tools that can enable rapid power curve measurements in the field could help reduce uncertainty when planning rural electrification programmes and ensure that small wind turbines are able to deliver vital energy services in off-grid regions of developing countries.